2009
DOI: 10.3109/03014460903325185
|View full text |Cite
|
Sign up to set email alerts
|

Study of the CTLA-4 gene polymorphisms in systemic lupus erythematosus (SLE) samples from Malaysia

Abstract: In this study, we investigated the polymorphisms of the exon 1 (+49A/G), promoter sites (-1722T/C, -1661A/G, -318C/T), and 3'-untranslated region (3'-UTR) (+6230 A/G) of the CTLA-4 gene in systemic lupus erythematosus (SLE) affected patients. Polymerase chain reaction-restriction fragment length polymorphism was used to determine genotypes of these five markers in 130 SLE patients and 130 healthy controls. Of the five tested polymorphisms, there was no statistical significant difference between the genotypic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 15 publications
3
21
3
Order By: Relevance
“…All amplifications were performed in a final volume of 20 mL containing 100 ng genomic DNA and appropriate PCR mixture, as previously described (Chua et al, 2009). Following that, PCR was performed in a thermal cycler according to the conditions described by Chua et al (2010).…”
Section: Genotypingmentioning
confidence: 99%
“…All amplifications were performed in a final volume of 20 mL containing 100 ng genomic DNA and appropriate PCR mixture, as previously described (Chua et al, 2009). Following that, PCR was performed in a thermal cycler according to the conditions described by Chua et al (2010).…”
Section: Genotypingmentioning
confidence: 99%
“…ECP is a specific marker of eosinophils (Ursaciuc et al, 2010;Shah et al, 2012;Beigelman, 2014;Smith et al, 2015), which is mainly activated and released by eosinophils and causes neurotoxicity and cytotoxicity. In addition, ECP induces release of histamine by mast cells, causing airway hyperresponsiveness, resulting in bronchial asthma attack (Reed et al, 2007;Choi et al, 2010;Chua et al, 2010;Ursaciuc et al, 2010;Wei et al, 2010;Braga et al, 2011;Olive et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Two polymorphic sites { + 49A/ G (rs231775) and CT60A/G (rs3087243)} were identified and used for the meta-analysis. Finally, 15 references were included in this research (Heward et al, 1999;Matsushita et al, 1999;Pullmann et al, 1999;D'Alfonso et al, 2000;Ahmed et al, 2001;Lee et al, 2001;Liu et al, 2001;Hudson et al, 2002;Aguilar et al, 2003;Barreto et al, 2004;Parks et al, 2004;Torres et al, 2004;Ulker et al, 2009;Chua et al, 2010;Kimkong et al, 2011). We subdivided the group of + 49A/G (rs231775) into Asia subgroup and Europe subgroup (five studies about Europe and eight studies about Asia).…”
Section: Ctla-4 Snp and Slementioning
confidence: 99%
“…The + 49A/G (rs231775) SNP causes an amino acid change from threonine to alanine in the peptide leader sequence of the CTLA-4 protein (Chistiakov and Turakulov, 2003), whereas CT60A/G (rs3087243) is important for efficient splicing and production of soluble CTLA-4, and may play a role in mRNA stability of sCTLA-4 (Ueda et al, 2003). A number of casecontrol studies have been conducted to investigate the association of these polymorphisms with SLE (Heward et al, 1999;Matsushita et al, 1999;Pullmann et al, 1999;D'Alfonso et al, 2000;Ahmed et al, 2001;Lee et al, 2001;Liu et al, 2001;Hudson et al, 2002;Aguilar et al, 2003;Barreto et al, 2004;Parks et al, 2004;Torres et al, 2004;Ulker et al, 2009;Chua et al, 2010;Kimkong et al, 2011). However, these studies have shown inconclusive or contradictory results.…”
Section: Introductionmentioning
confidence: 99%